2018
DOI: 10.22452/mjs.vol37no1.5
|View full text |Cite
|
Sign up to set email alerts
|

Α-Glucosidase INHIBITORY EFFECT OF SULOCHRIN FROM ASPERGILLUSTERREUS AND ITSBROMINATED DERIVATIVES

Abstract: Use of α-glucosidase inhibitorsis one of the therapeutic approaches for decreasing postprandial hyperglycemia. Sulochrin (1) from Aspergillus terreus as well as two synthetic sulochrin derivatives were assessed for antidiabetic activity against yeast and rat intestine α-glucosidase. Sulochrin showed potential inhibition against yeast α-glucosidase, through a non-competitive mode with an IC 50 value of 133.79 µM, and rat intestine α-glucosidase by uncompetitive mode with an IC 50 value of 144.59 µM.. Two synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Reported α -glucosidase activities regarding several A. terrus -isolated metabolites within our literature review [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] have prompted us to further investigate the potentiality of identifying novel uncited hits with potential biological activity. Additionally, exploring the molecular aspects of the compound’s affinity/binding with human α -glucosidase biological targets through a sophisticated in silico study was rationalized in order to guide future lead optimization and development.…”
Section: Resultsmentioning
confidence: 99%
“…Reported α -glucosidase activities regarding several A. terrus -isolated metabolites within our literature review [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] have prompted us to further investigate the potentiality of identifying novel uncited hits with potential biological activity. Additionally, exploring the molecular aspects of the compound’s affinity/binding with human α -glucosidase biological targets through a sophisticated in silico study was rationalized in order to guide future lead optimization and development.…”
Section: Resultsmentioning
confidence: 99%
“…Previous our study has shown that fungi of Aspergillus sp, can produce an α-glucosidase inhibitors. Butyrolactone I, II, and three synthetic butyrolactone I derivatives were isolated from A. Terre us MC751 cultured in Czapek-dox broth, showed potential activity toward α-glucosidase (Dewi, et al, 2014), sulochrin and its brominated derivated also produced by A. terreus RCC1 by solid state fermentation exhibition of significant activity against α-glucosidase (Dewi, et al, 2018) and rubrofusarin showed potential activity inhibited of mamalian α-glucosidase, which isolated from A. aculeatus cultured in potato dextrose broth (Dewi, et al, 2016). Continuing of our efforts to isolate potential a-glucosidase inhibitors from terestrial fungi, the objective of this study was to isolated active compound from A. terreus F38 which cultured in potato dextrose broth.…”
Section: Introductionmentioning
confidence: 99%